Adaptation and Strategic Retirement of Secondary School Teachers - Obella, Elisha; Kigozi Munene, John C.; Mpeera Ntayi, Joseph; Kagaari, James (Public Organization Review, 2021)
This study explains strategic retirement amongst Uganda’s secondary school teachers using work adjustment and development theories. Data relating to psychological adaptation and socio cultural adaptation were attained using a cross-sectional quantitative approach. Primary data was collected using a self-administered questionnaire from 356 responses were received out of the 381 questionnaires that were distributed in 112 secondary schools in western and eastern Uganda. Data were analyzed using Statistical Program for Social Sciences (SPSS) and Analysis of Moment Structures (AMOS). The authors found that there a significant positive relationship between adaptation and strategic retirement amongst Uganda’s secondary school teachers.
Keywords: Adaptation; Strategic retirement; Secondary schools; Work adjustment; Uganda